2022
DOI: 10.1177/00368504221079180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sealing performance of a compression packer at high temperature

Abstract: Rubber is the key component of a compression packer, which directly affects the success or failure of seals. Presently, the contact stress between the rubber and borehole walls is used as the main evaluation criterion for the sealing ability of the rubber of the compression packer. However, this evaluation criterion is imperfect. This study establishes the sealing performance and reliability evaluation system of a compression packer at 120°C. Considering the influence of time and temperature on the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The new findings extended our previous works 14,15 to more complex geometry and compression of HNBR downhole packer using fundamental material behavior such as viscoelasticity, hyperelasticity, chemical degradation based on laboratory tests, and FEA for long-term sealing application. The current study has additional consideration of fluid aging for a long-term operation to conventional FEA analysis of packer rubber studied by Zheng et al 16,17 and Chen et al 18 The proposed FEA methodology by chemical aging is not limited to the size of the elastomer shape and can be readily extended to develop a successful operation limit for various elastomer applications in the energy industry.…”
Section: Analysis Of the Operational Limitmentioning
confidence: 99%
See 2 more Smart Citations
“…The new findings extended our previous works 14,15 to more complex geometry and compression of HNBR downhole packer using fundamental material behavior such as viscoelasticity, hyperelasticity, chemical degradation based on laboratory tests, and FEA for long-term sealing application. The current study has additional consideration of fluid aging for a long-term operation to conventional FEA analysis of packer rubber studied by Zheng et al 16,17 and Chen et al 18 The proposed FEA methodology by chemical aging is not limited to the size of the elastomer shape and can be readily extended to develop a successful operation limit for various elastomer applications in the energy industry.…”
Section: Analysis Of the Operational Limitmentioning
confidence: 99%
“…FEA analysis for HNBR for packer rubber was conducted on compression rate, liner pressure, surface pressure, and sealing performance coefficient. 16 Stress relaxation effect on sealing performance of packer rubber was studied. 17 The results indicated that the temperature and stress relaxation had an appreciable impact on the sealing performance of a packer rubber seal system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydraulic fracturing is one of the methods for measuring in-situ stress specified by the International Professional Committee of Rock Mechanics Testing Technology, and it is also the most effective method for measuring deep in-situ stresses. At present, the differential pressure of some newly developed bridging packers in the world is around 35 MPa, which cannot fully meet the temperature and pressure conditions required for deep hole geostress testing (Wakuda et al, 2002;Zhao et al, 2021a;Zhao et al, 2021b;Liu et al, 2022;Zhao et al, 2022;Zheng et al, 2022). Packers are important tools for downhole stress measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the performance of the rubber cartridge, some scholars have carried out related research on the selection and design of the packer (Lan et al, 2019;Liu et al, 2020;Zheng et al, 2022). However, in the research on the improvement of the rubber tube structures of the packer and the selection of rubber materials, there is no systematic analysis of the influence of different lithologies on the adaptability of the packer.…”
Section: Introductionmentioning
confidence: 99%